The Hubungan Kondisi Psikososial Dan Paritas Dengan Kejadian Depresi Postpartum Pada Ibu Remaja - Ariani Fatmawati; Nina Gartika (Faletehan Health Journal, 2021)
The incidence of postpartum depression in adolescent mothers is increased every year. Unpreparedness in accepting the new role is one of the causes of this increase. Previous studies have found factors that influence the incidence of postpartum depression; however, specific studies that discuss the relationship between psychosocial conditions and parity with postpartum incidence are still very limited. The purpose of this study was to determine the psychosocial condition and parity with the incidence of postpartum depression. This is a quantitative research with cross-sectional method to analyze the independent variables by the dependent variables. The samples were taken by consecutive sampling of 90 mothers. The bivariate data was analyzed by using chi-square. The results showed a significant relationship between psychological conditions and the incidence of postpartum depression (p = 0.007); while there is no relationship between parity and the incidence of postpartum depression (p = 0.180). The results of this study can be used as an input for health workers to screen postpartum depression during pregnancy.